2013
DOI: 10.1016/j.matdes.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of local variations in mechanical behaviour – Numerical investigation of a ductile iron component

Abstract: The effects of incorporating local mechanical behaviour into a structural analysis of a cast ductile iron component are investigated. A recently presented simulation strategy, the closed chain of simulations for cast components, is applied to incorporate local behaviour predicted by a casting process simulation into a Finite Element Method (FEM) structural analysis, and the effects of the strategy on predicted component behaviour and simulation time are evaluated. The results are compared to using a homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…one material definition for every element of the FEM mesh. This software has previously been applied to create element individual material definitions for cast components based on casting process simulation results [16,18,37]. In this work, characterisation models relating the coarseness of the microstructure and the local mechanical behaviour were established using the tensile testing results.…”
Section: Fem Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…one material definition for every element of the FEM mesh. This software has previously been applied to create element individual material definitions for cast components based on casting process simulation results [16,18,37]. In this work, characterisation models relating the coarseness of the microstructure and the local mechanical behaviour were established using the tensile testing results.…”
Section: Fem Simulationmentioning
confidence: 99%
“…The simulation strategy includes characterisation models developed for cast iron [17] and sand cast aluminium alloys [2,3], whereas models for High Pressure Die Cast (HPDC) aluminium alloys have not been previously established. A numerical investigation of a ductile iron component using the proposed simulation strategy has shown that the predicted behaviour of the component when subjected to load is significantly affected by local variations in mechanical behaviour, which cause a redistribution of stresses and strains that it is impossible for a model in a homogenous material to predict [18]. However, this effect has only been predicted numerically, not confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important difference from the results reported in in the previous study of a ductile iron component. 21,22) The Young's modulus in cast iron is related to the chemical composition of the alloy and the morphology of the graphite precipitates. 24) In ductile iron variations in solidification conditions cause variations in graphite morphology, thus a variation in Young's modulus is obtained throughout a ductile iron component.…”
Section: Mechanical Behaviourmentioning
confidence: 99%
“…In previous work the simulation strategy has been applied to a ductile iron component. 21,22) The strategy has however not been previously applied to a cast aluminium component.…”
Section: Introductionmentioning
confidence: 99%
“…Another chance of reducing the part weight is the maximum utilization of the material's performance by an exact characterization of the material behavior. Therefore, the knowledge of local mechanical properties enables an accurate validation of processand part design to extend the process limits [1]. Especially, the variation of local material behavior of a part can be characterized for the validation of a numerical simulations [2].…”
Section: Introductionmentioning
confidence: 99%